EFFICACY OF INTRA OPERATIVE USE OF TRIAMCINOLONE IN LUMBAR DISCECTOMY - Ishfaq, Asim; Shahzad, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the effect of epidural application of triamcinolone during lumbar discectomy onpostoperative pain relief.Study Design: Case control study.Place and Duration of Study: Department of Neurosurgery, Combined Military Hospital Lahore, from Oct 2019to Feb 2020.Methodology: Thirty patients receiving intraoperative epidural triamcinolone application compared with30 controls objective assessment by T-scores of the Timed Up and Go test, back and sciatic leg pain by Visualanalog scale and for subjective functional impairment by oswestry Disability Index were calculated pre-op, postoperative day 2 and at 4 weeks.Results: The baseline demographics, disease specific features and preoperative impairment scores were similaramong both groups. At day post-operative day 2, subjective impairment on oswestry disability index for thesteroid group was (30.6 vs 36.2, p